PENGARUH PRENATAL YOGA TERHADAP PENURUNAN NYERI PUNGGUNG IBU HAMIL TRIMESTER III DI WILAYAH KERJA PUSKESMAS SEI LANGKAI KOTA BATAM TAHUN 2026 - Desi Ernita Amru; Siti Husaidah (Zona Kebidanan: Program Studi Kebidanan Universitas Batam, 2026)
Back pain is a common complaint experienced by third-trimester pregnant women due to physiological changes such as weight gain, postural changes, and ligament relaxation. This condition can interfere with comfort and daily activities, therefore requiring safe and effective management, one of which is a non-pharmacological therapy in the form of prenatal yoga. This study aimed to determine the effect of prenatal yoga on reducing back pain among third-trimester pregnant women in the working area of Sei Langkai Public Health Center, in 2026. This research is a Quasi-Experiment using a Pre-test – Post-test with control group design. The population in this study consisted of 2,586 third-trimester pregnant women in the Sei Langkai Health Center working area, Batam City. The sampling technique used was purposive sampling, resulting in a sample of 17 pregnant women experiencing back pain. Data collection involved both primary and secondary data, analyzed using the Paired T-test. The results showed that before the intervention, the majority of respondents (8 women or 47%) experienced moderate pain, which decreased after the intervention, with 14 women (82%) reporting a shift within the moderate-to-lower pain intensity range. The T-test results yielded a p-value of 0.003 (p < 0.05), indicating a significant effect of prenatal yoga on reducing back pain in third-trimester pregnant women. In conclusion, prenatal yoga is effective in lowering back pain levels and can be implemented as a safe and beneficial non-pharmacological intervention in antenatal care services to enhance maternal comfort